GOLD Observations of Longitudinal Variations in the Nighttime Equatorial Ionization Anomaly (EIA) Crests' Latitudes. Issue 4 (15th April 2023) - Eastes, R. W.; Karan, D. K.; Martinis, C.; Daniell, R. E.; Gan, Q.; Burns, A. G.; McClintock, W. E.
Abstract: Each day the Global‐scale Observations of the Limb and Disk imager observes the equatorial ionization anomaly (EIA) near sunset from ∼10°E to ∼80°W geographic longitude. Most images cover ∼45° of longitude (∼3 hr), and most longitudes are observed multiple times. Monthly averages of EIA crests' latitude (EIA lats) versus longitude during March, September, and December 2020 have been analyzed. The EIA lats reflect the combined influence of winds, solar radiation, and fields (electric and magnetic) in the equatorial region. Winter solstice differs significantly from the equinoxes, which are similar, but there are notable similarities between all three. The similarities in the EIA lats during the seasons examined indicates that the magnetic equator to subsolar point separation influences them in all three seasons and that it has a more distinct, possibly more significant, influence than winds on the average latitudes. Plain Language Summary: Each day the Global‐scale Observations of the Limb and Disk imager observes the nighttime equatorial ionization anomaly (EIA) near sunset as the terminator progresses westward from Africa to across South America. Most images cover ∼45° of longitude (∼3 hr of local time), and most longitudes are observed multiple times. In 2020 seasonal averages of the crests' latitude versus longitude during the equinoxes (March and September) and winter solstice (December) show significant, important similarities. The observed latitude versus longitude dependence in all three show a dependence on the distance between the magnetic equator and the subsolar point. Greater knowledge of the seasonal‐longitudinal dependence of the EIA crests' latitudes contributes significantly to understanding the crests' response to fields (electric and magnetic) and winds in the equatorial region. Key Points: The average nighttime EIA crests' latitudes observed by GOLD during 2020 equinoxes and December solstice have a longitudinal dependence Crests' latitude dependence on longitude changes near 47°W geographic, where the magnetic and geographic equators cross Crests' latitudes over 75°W–10°E geographic longitude during equinoxes and winter solstice depend on the subsolar point magnetic latitude